التقصي عن انتشار فيروسي موزاييك الخيار وموزاييك الفصة على نباتات الخبيزة (Malva sp.)في محافظتي اللاذقية وطرطوس - راعي, سليم (Latakia University Journal -Biological Sciences Series, 2019)
أثبت الفحص المصلي باستخدام اختبار البصمة النسيجية المناعية (TBIA)لـ 384 عينة, انتشار فيروسي موزاييك الفصة وموزاييك الخيار على نباتات الخبيزة في مناطق مختلفة من محافظتي اللاذقية وطرطوسوكانت نسبة الإصابة 9.9%, 5.5% على التوالي. وكانت أعلى نسبة انتشار لفيروس CMV في اللاذقية في منطقة فديو (9.38%) ولفيروس AMV في منطقة وادي قنديل (15.63%) بينما في طرطوس كانت أعلى نسبة في منطقة الصفصافة 9.38% وفي البصيصه (18.75%) على التوالي. تم نقل الإصابة بفيروس موزاييك الخيار وموزاييك الفصة من نباتات الخبيزة بواسطة العدوى الميكانيكية إلى مجموعة من النباتات الدالة, وكانت الأعراض التي ظهرت عليها متوافقة معالأعراض التي يسببها كل من الفيروسين, وأثبت اختبار البصمة النسيجية المناعية وجودها في العينات التي حضّر منها اللقاح وفي العينات المأخوذة من النباتات الدالة. تعد هذه النتيجة التسجيل الأول محلياً لوجود فيروس موزاييك الفصة على نباتات الخبيزة. Serological test of 384 samples using Tissue blot immunobinding Assay (TBIA) has proved the distribution of Alfalfa mosaic and Cucumber mosaic viruses on Common Mallow Malva sp. plants in several regions of Lattakia and Tartous Provinces in a ratio of 9.9% and 5.5% respectively. The highest ration of CMV transmission was recorded in Fedio in Lattakia (9.38%) and AMV in WadyKandeel region (15.63%), whereas they were recorded in Elsafsafeh and EL-basasah regions in Tartous 9.38% and 8.75% respectively. Infection by Alfalfa mosaic and Cucumber mosaic viruses has been transmitted mechanically from infected Common Mallow plant to several indicator plants which showed exact symptoms of tested viruses. Tissue blot immunobinding Assay has proved the existence of tested viruses in plants used for inoculums preparation. This is the first local record of Alfalfa mosaic virus on Common Mallow Malva sp. plants in Syria.